If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8x + 6 = 11x + -24 Reorder the terms: 6 + 8x = 11x + -24 Reorder the terms: 6 + 8x = -24 + 11x Solving 6 + 8x = -24 + 11x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-11x' to each side of the equation. 6 + 8x + -11x = -24 + 11x + -11x Combine like terms: 8x + -11x = -3x 6 + -3x = -24 + 11x + -11x Combine like terms: 11x + -11x = 0 6 + -3x = -24 + 0 6 + -3x = -24 Add '-6' to each side of the equation. 6 + -6 + -3x = -24 + -6 Combine like terms: 6 + -6 = 0 0 + -3x = -24 + -6 -3x = -24 + -6 Combine like terms: -24 + -6 = -30 -3x = -30 Divide each side by '-3'. x = 10 Simplifying x = 10
| tan29=27/x | | -25x(-4)x(-2)= | | 14x+3=11x-12 | | 9x-8=5x-28 | | 12x+9=4x+57 | | 11x+11=8x+20 | | 3x+20=7x-6 | | 1.3k+3.7=8 | | 34m=20.4 | | 14x+11=7x-3 | | 11x+7=4x+77 | | x^2+7x+2 = 2 | | 7x+8=10x-22 | | -4/7x5 | | 10x-11=3x-25 | | 15x+3=3x+51 | | 7x-8=3x-16 | | 15x-9=4x+68 | | 9x-6=6x+21 | | -19-2y=17+7y | | 4x-11=6x-19 | | 9x+11=10x+14 | | (4x+10)=3 | | 15x-11=7x-51 | | 12x+6=6x+72 | | 11x-12=12x-9 | | 2x^3-5x+8=0 | | 6x+10=9x-5 | | X/5-75=116 | | 2y-4(-6z+3y)-5z=0 | | 12x-8=9x+25 | | 15x-4=9x+32 |